2021
DOI: 10.1371/journal.pone.0249935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray-drying and ultraviolet C radiation as biosafety steps for CSFV and ASFV inactivation in porcine plasma

Abstract: Spray-dried animal plasma (SDAP) is widely used in diets of domestic animals to improve health status and increase growth and feed efficiency. Individual steps in the SDAP manufacturing process, including spray-drying, have been validated to inactivate potential pathogens. Manufacturing standards have established a minimum exit temperature of 80°C and a minimum post-drying storage period of 14 days at 20°C for production of SDAP. Also, UV-C irradiation has been evaluated as another inactivation step that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Both CCPs rely on a combination of dehydration and dry-heat phenomena to reduce virus infectivity. Results from published studies ( 6 , 20 , 22 , 34 ) have shown that spray drying in addition to extended storage (i.e., SD + extended storage) are capable of inactivating a wide range of naked and enveloped RNA and DNA swine viruses. The risk assessment model showed mean inactivation levels of PEDV and ASFV ranged from 8.4 to 11.1 log ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both CCPs rely on a combination of dehydration and dry-heat phenomena to reduce virus infectivity. Results from published studies ( 6 , 20 , 22 , 34 ) have shown that spray drying in addition to extended storage (i.e., SD + extended storage) are capable of inactivating a wide range of naked and enveloped RNA and DNA swine viruses. The risk assessment model showed mean inactivation levels of PEDV and ASFV ranged from 8.4 to 11.1 log ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, results from these studies showed that enveloped viruses are more sensitive to ultraviolet C irradiation than non-enveloped viruses, but infectivity is reduced by at least 4 logs. Furthermore, although spray drying effectively inactivates at least 4 logs of ASFV and CSFV, the use of ultraviolet C irradiation within the spray drying process can provide additional inactivation of ASFV by more than a 4 log TCID 50 /mL reduction [80].…”
Section: Process Range In Temperature and Time Resultsmentioning
confidence: 99%
“…Spray-dried animal plasma contains many functional compounds, including immunoglobulins, albumin, fibrogen, lipids, growth factors, biologically active peptides, transferrin, enzymes, and hormones [80], that play a positive role in the immune sys-tem [122], especially in weaned pigs undergoing a disease challenge [123]. Blázquez et al [79] collected unprocessed liquid-porcine-plasma-contaminated ASFV from the blood of infected pigs, blended it with feed to achieve an infectious dose of 10 4 or 10 5 TCID 50 , and fed the contaminated feed for 14 consecutive days to determine if it would cause infection in naïve weaned pigs in two separate experiments.…”
Section: Animal Plasmamentioning
confidence: 99%
“…On the other hand, the manufacturing process of SDP and SBI has been extensively investigated to inactivate microorganism of concern for either human or animal consumption [8]. In case of African Swine Fever virus (ASFV), recent publications [9,10] demonstrated that the different steps involved in the manufacturing process of SDP or SBI (spray-drying and storage at 20 • C for 14 days) can be considered robust inactivation steps according to World Human Organization (2004) guidelines for human plasma transfusion. Furthermore, with regard to the risk of bovine spongiform encephalopathy (BSE) of prions in the collected blood, in the case of blood from pigs there is no risk of prions diseases because encephalopathies has not been established in natural conditions in commercial pigs [11] and, in the case of bovine origin, blood is not considered specific risk material according to the OIE and, in fact, blood and blood products, such as SBI or SDP, are included in the list of safe commodities like milk [12].…”
mentioning
confidence: 99%